Static and fluctuating magnetic moments in the ferroelectric metal LiOsO3 - Kirschner, F; Lang, F; Pratt, F; Lancaster, T; Shi, Y; Guo, Y; Boothroyd, A; Blundell, S (Physical Society of Japan 日本物理学会, 2018)
LiOsO3 is the first example of a new class of material called a ferroelectric metal. We performed zero-field and longitudinal-field μSR, along with a combination of electronic structure and dipole field calculations, to determine the magneticground state of LiOsO3. We find that the sample contains both static Li nuclear moments and dynamic Os electronic moments. Below ≈0.7 K, the fluctuations of the Os moments slow down, though remain dynamic down to 0.08 K. We expect this could result in a frozen-out, disordered ground state at even lower temperatures.